2021
DOI: 10.1115/1.4051546
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of the Superlubricity Behavior of Polyimide-Induced Liquid Crystal Alignment

Abstract: We have studied the friction behavior based on liquid crystal (LC) alignment of a unique tribological system composed of a nematic LC and polyimide (PI). The LC was used as a lubricant and a tribological factor with molecular alignment ability. PI was used as both a rubbing pair part and a LC alignment agent. The LCs used as lubricants included the single LC 5CB and the mixed LCs 5CB–2UTPP3 and 3PEP5–3UTPP4. The PI used as the friction pair was 6FDA-ODA PI, and its counterpart was GCr15 steel. For this system,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The formation of this intermediary layer is largely influenced by the molecular structure of the lubricant. A study by Gao et al [ 35 ] demonstrated that certain lubricants, due to their unique molecular structures, could align themselves to form highly ordered ‘liquid crystals’ at the interface, effectively reducing the contact area between the surfaces, and thus enabling superlubricity.…”
Section: Mechanics Of Superlubricitymentioning
confidence: 99%
“…The formation of this intermediary layer is largely influenced by the molecular structure of the lubricant. A study by Gao et al [ 35 ] demonstrated that certain lubricants, due to their unique molecular structures, could align themselves to form highly ordered ‘liquid crystals’ at the interface, effectively reducing the contact area between the surfaces, and thus enabling superlubricity.…”
Section: Mechanics Of Superlubricitymentioning
confidence: 99%
“…It is widely recognized that the key to achieving liquid superlubricity is to ensure that the liquid molecules are stabilized on the surface of the friction pair under external pressure while providing very low shear strength [ 34 ]. Through the initial exploration of liquid superlubricity systems, our team also discovered a superlubricity system using nematic liquid crystals (LCs) as the lubricant and GCr15 steel with PI as the friction pair [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we tested a system with a PI film and GCr15 steel as the friction pair and nematic LCs as the lubricant and found that friction led to the alignment of PI, and aligned PI induced the orientation of LCs in the grooves of PI wear scars, resulting in the stable superlubricity property of the system [ 35 , 36 ]. For this type of superlubricity system, the alignment of PI and LCs is very important.…”
Section: Introductionmentioning
confidence: 99%